The Effect of Providing Non-Cognitive Diagnostic Assessments and Realistic Mathematics Learning Approaches to Improve Students' Mathematical Literacy Skills - Winda Maria Erwinda Kefi; Cecilia Novianti Salsinha; Justin Eduardo Simarmata (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to determine the effect of providing non-cognitive diagnostic assessments and Realistic Mathematics Education (RME) on improving students' mathematical literacy skills. This study applies a quasi-experimental method with a 2x2 factorial-based research design. Grade VIII students at Naiola State Junior High School were the population and sample in this study. The results of this study show that (1) there are differences in mathematical literacy skills between students who are given non-cognitive diagnostic assessments (students with very high, adequate, low and very low interest in learning); (2) there is a difference in students' mathematical literacy skills between students who are taught conventionally); (3) there is significant interactivity between non-cognitive diagnostic assessments and learning approaches to students' mathematical literacy skills. Thus, non-cognitive diagnostic assessments combined with realistic mathematical learning approaches have an effect on improving students' mathematical literacy skills compared to other treatments.